Comparison of CpG Distribution in Methylation Sensitive and Methylation Resistant CpG Islands and Study the Effect on Methylation - Shivangi (My University, 2014)
The organization of eukaryotic DNA is highly diversified and it includes certain CpG rich sequences called CpG Islands. These CpG Islands are found to be unmethylated usually and occasionally methylated. The methylation is centered on the dinucleotide CpG. Most of the CpG Islands are known to be associated with the promoter region of the genes and are usually unmethylated. Lately, it has been found that CpG Islands exhibit varying propensity to get methylated. They can be fully methylated or unmethylated, thereby may be considered as methylation sensitive or methylation resistant. In the present work, a comparative study based on DNA sequence attributes has been performed to find out why certain CpG Islands tend to get methylated. The abundance or under-representation of tri- and tetranucleotide permutations has been investigated in the two classes of CpG Islands viz.,fully methylated and unmethylated. Further ∆Gfolding and relative abundance of inverted repeats has also been studied to find any bearing on CpG Island methyation. Finally distribution of CpGs in the CpG Islands has been analyzed. All the four factors were statistically analyzed and they appear to be significantly different in the two classes of CpG Islands and thus can be speculated to influence the methylation of CpG Islands.
M.Sc- Biotechnology -Dissertation
Keywords: DNA methylation; CpG islands; methylation sensitive